Eye banking and keratoplasty trend analysis during the COVID-19 pandemic: A South Indian observational study - Aditee Madkaiker; Anitha Venugopal; Aditya Ghorpade; Meenakshi Ravindran; Ramakrishnan Ragappa; Mohammed Uduman Sithiq (Indian Journal of Ophthalmology, 2023)
Purpose: To analyze the impact on eye donation and corneal transplantation during the COVID-19 pandemic in a tertiary eye hospital in south India. Methods: A retrospective analysis of the donor and recipient records during the study period from January 2020 to May 2021 was conducted and tabulated in Microsoft Excel 2013. Demographic details of the donor, utility rate, cause of death, culture characteristics, storage methods, wet lab usage, and the surgical donor outcomes were evaluated. Additionally, the postoperative workup of the recipients, diagnosis, graft infection and rejection episodes, development of COVID-19 postoperatively, and outcome in terms of visual acuity at one, three, and six months were also noted. Results: A total of 466 eyes from 249 donors were received during the study period. The mean age of the donor population was 62.43 years (20.9). The corneal transplantation utility rate was 36.4% (n = 170). Fifty-one percent of the total transplant surgeries were for therapeutic purposes. This was followed by penetrating optical keratoplasty (34%), Descemet's stripping endothelial keratoplasty (9%), and patch grafts (3%). Seventeen (10%) graft rejection episodes were noted and nine (53%) had complete resolution after medical treatment. Conclusion: Proper preventive measures are key to carrying out safe and efficient eye banking activities even during a deadly pandemic, as COVID-19 transmission via transplantation is rare.